DATA STORAGE AND DIGITAL SOVEREIGNTY. A REINTERPRETATION OF PUBLIC (BIG) DATA GOVERNANCE IN THE LIGHT OF NEW GLOBAL CHALLENGES - Valentina Pagnanelli (Revista Direito Mackenzie, 2022)
Using data retention policies in the public sector as a paradigm, the paper reflects how States assert or defend their digital sovereignty. The article recalls the digitization path of the Italian PA, on which big data has had a significant impact. Digital data storage has imposed the transition from paper archives to the cloud, a transition regulated by national and European legislation and partly influenced by the digital strategies of the great world powers. The proliferation of localization obligations and prohibitions confirms the complexity and centrality of these issues in protecting digital sovereignty. The paper ends with an analysis of the key points of the European strategy for data published by the European Commission in February 2020 and with a look at the Franco-German data storage and data sharing project called GAIA-X.